The Role of Advertisements in English Foreign Language (EFL) Teaching - Farida Hanim Saragih; Citra Anggia Putri (Universitas Negeri Medan, 2015)
This paper aims at discussing the use of advertisements (ads) in English Foreign Language (EFL) teachingand focuses on some of the appealing uses of language, visual elements, and culture in advertising, and onhow language teachers could exploit them in their classes. Advertisers have creative ways to use ads toattract people’s attention and to be memorable by exploiting the language code, paralanguage, illustrationand culture value. The ways of advertisers to use the language, illustration, code, and culture could beconsidered by the language teachers in teaching. Language teachers appears to be very little exploitationof the fascinating uses of language and visual elements in advertising, and this paper attempts to presentEFL practice by providing an overview of some of the interesting uses of language, culture, and visualelements in ads, and suggesting ways of exploiting them in classroom